2016
DOI: 10.1111/eos.12279
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between intra‐oral cinnamaldehyde and nicotine assessed by psychophysical and physiological responses

Abstract: Cinnamaldehyde and nicotine activate the transient receptor potential subtype A1 (TRPA1) channel, which may cause burning sensations. This study investigated whether cinnamaldehyde modulates nicotine-induced psychophysical and physiological responses in oral tissues. Healthy non-smokers (n = 22) received, in a randomized, double-blind, crossover design, three different gums containing 4 mg of nicotine, 20 mg of cinnamaldehyde, or a combination thereof. Assessments of orofacial temperature and blood flow, blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 43 publications
4
11
2
Order By: Relevance
“…Interestingly, menthol alone evoked burning sensations and pain, albeit to a lower degree than nicotine, in approximately half of the study participants, and further, these participants reported more intense burning and irritation when menthol and nicotine were applied in combination (Nielsen et al, 2016 ). In a subsequent study, we found a similar result for cinnamaldehyde alone and in combination with nicotine (Jensen et al, 2016 ).…”
Section: Introductionsupporting
confidence: 80%
See 4 more Smart Citations
“…Interestingly, menthol alone evoked burning sensations and pain, albeit to a lower degree than nicotine, in approximately half of the study participants, and further, these participants reported more intense burning and irritation when menthol and nicotine were applied in combination (Nielsen et al, 2016 ). In a subsequent study, we found a similar result for cinnamaldehyde alone and in combination with nicotine (Jensen et al, 2016 ).…”
Section: Introductionsupporting
confidence: 80%
“…In contrast to menthol and nicotine, cinnamaldehyde is the most selective TRPA1 agonist, is known to produce burning sensations and pain (Namer et al, 2005 ) and is the aldehyde that gives cinnamon its taste. Contrary to expectations, our previous study showed cinnamaldehyde in combination with nicotine did not exert a synergistic effect on intra-oral burning or irritation intensities (Jensen et al, 2016 ). However, individuals responding to cinnamaldehyde as an irritant demonstrated larger areas of nicotine evoked irritation in the throat (Jensen et al, 2016 ).…”
Section: Introductioncontrasting
confidence: 79%
See 3 more Smart Citations